Creación de un centro de acopio de leche para fomentar el desarrollo socio-económico, financiero en el barrio San Ramón, parroquia Mulaló - Lescano Almache, María del Carmen (2015)
The creation of a central milk storage is important, since this liquid is within the daily feeding of all human beings and most of it is regarded as the essential raw material for the processing and transformation of it into the dairies. As a primary product milk for changing the productive matrix and noted the large number of people dedicated to livestock in the area of San Ramon, the idea to create a milk collection center that stores and bid a quality product….